Joint multipath signals and noise reduction in passive radar - Xiaoyong Lyu; Yingqiang Ding (IET Signal Processing)
Abstract The paper considers the multipath signal and noise reduction problem in passive radar. A unified framework is provided for the joint reduction of multipath signals and noise in both Gaussian and non‐Gaussian circumstances. The traditional clutter cancellation methods are incorporated in this framework corresponding to the Gaussian circumstance. Based on this framework, a joint reduction method (JRM) is developed for suppressing the multipath signals and noise. Specifically, the cancellation of noise is explicitly discussed. Analytical analysis of the proposed method is included. An approximate implementation of the JRM (approximate implementation of the joint reduction method) which increases the computational efficiency is also provided. Simulations demonstrate the effectiveness of the proposed methods.